2022
DOI: 10.1111/twec.13273
|View full text |Cite
|
Sign up to set email alerts
|

Investment incentives and leverage: Evidence from China’s accelerated depreciation policy

Abstract: Using a difference‐in‐differences (DID) approach, this paper evaluates the effects of China's accelerated depreciation policy on corporate leverage. We find that the policy significantly increases corporate total leverage, which is mainly driven by the increase in long‐term leverage. Moreover, raising investment in fixed assets serves as the primary mediating channel through which the policy affects long‐term leverage and thus, total leverage. Finally, the positive effects of the policy on leverage are primari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 60 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…Accelerated depreciation is an important part of the COVID-19 response around the world. However, the abuse of tax incentives may lead to a spike in corporate leverage and even trigger systemic financial risks (Zhao and Fang, 2022b). In addition to the danger of high leverage, the risk of maturity mismatch between financing and investment also cannot be ignored (Bai, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accelerated depreciation is an important part of the COVID-19 response around the world. However, the abuse of tax incentives may lead to a spike in corporate leverage and even trigger systemic financial risks (Zhao and Fang, 2022b). In addition to the danger of high leverage, the risk of maturity mismatch between financing and investment also cannot be ignored (Bai, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have rigorously evaluated the investment eff ect of ADP and found that ADP has indeed had positive impacts on business investment (Zwick and Mahon, 2017;Ohrn, 2019;Fan and Liu, 2020). Corporate internal funds are not likely to cover the capital required for these investments, so firms need external fi nancing (Zhao and Fang, 2022b). Further, combined with other determinants of corporate debt maturity structure, fi rms determine their optimal fi nancing maturity structure and then apply for loans from banks.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation